An ultra‐black silicon absorber. Issue 2 (15th January 2014) - Steglich, Martin; Lehr, Dennis; Ratzsch, Stephan; Käsebier, Thomas; Schrempel, Frank; Kley, Ernst‐Bernhard; Tünnermann, Andreas
<x xml:space="preserve">Abstract</x> An ultra‐black (A > 99%) broadband absorber concept on the basis of a needle‐like silicon nanostructure called Black Silicon is proposed. The absorber comprises Black Silicon established by inductively coupled plasma reactive ion etching (ICP‐RIE) on a highly doped, degenerated silicon substrate. Improved absorbers also incorporate an additional oxide capping layer on the nanostructures and reach an absorptance of A > 99.5% in the range of 350 to 2000 nm and A ∼ 99.8% between 1000 and 1250 nm. Fabrication of the absorbers is consistent with CMOS standards and requires no lithography. (Picture: Kasper, Friedrich‐Schiller‐University Jena) <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>